Tolerance response of multidrug-resistant Salmonella enterica strains to habituation to Origanum vulgare L. essential oil - Monte, Daniel F. M.; Tavares, Adassa G.; Albuquerque, Allan R.; Sampaio, Fábio C.; Oliveira, Tereza C. R. M.; Franco, Octavio L.; Souza, Evandro L.; Magnani, Marciane (Frontiers in Microbiology, 2014)
Multidrug-resistant Salmonella enterica isolates from human outbreaks or from poultry origin were investigated for their ability to develop direct-tolerance or cross-tolerance to sodium chloride (NaCl), potassium chloride (KCl), lactic acid (LA), acetic acid (AA) and ciprofloxacin (CIP) after habituation in subinhibitory amounts (½ of the minimum inhibitory concentration - ½ MIC and ¼ of the minimum inhibitory concentration - ¼ MIC) of Origanum vulgare L. essential oil (OVEO) at different time intervals. The habituation of S. enterica to OVEO did not induce direct-tolerance or cross-tolerance in the tested strains, as assessed by the modulation of minimum inhibitory concentration (MIC) values. However, cells habituated to OVEO maintained or increased susceptibility to the tested antimicrobials agents, with up to four-fold double dilution decrease from previously determined MIC values. This study reports for the first time the non-inductive effect of OVEO on the acquisition of direct-tolerance or cross-tolerance in multidrug-resistant S. enterica strains to antimicrobial agents that are largely used in food preservation, as well as to CIP, the therapeutic drug of salmonellosis.